Osteoarthritis year in review 2019: imaging - Kijowski, R.; Demehri, S.; Roemer, Frank; Guermazi, A. (Osteoarthritis and Cartilage, 2020)
Objective: To provide a narrative review of original articles on osteoarthritis (OA) imaging published between April 1, 2018 and March 30, 2019. Methods: All original research articles on OA imaging published in English between April 1, 2018 and March 30, 2019 were identified using a PubMed database search. The search terms of “Osteoarthritis” or “OA” were combined with the search terms “Radiography”, “X-Rays”, “Magnetic Resonance Imaging”, “MRI”, “Ultrasound”, “US”, “Computed Tomography”, “Dual Energy X-Ray Absorptiometry”, “DXA”, “DEXA”, “CT”, “Nuclear Medicine”, “Scintigraphy”, “Single-Photon Emission Computed Tomography”, “SPECT”, “Positron Emission Tomography”, “PET”, “PET-CT”, or “PET-MRI”. Articles were reviewed to determine relevance based upon the following criteria: 1) study involved human subjects with OA or risk factors for OA and 2) study involved imaging to evaluate OA disease status or OA treatment response. Relevant articles were ranked according to scientific merit, with the best publications selected for inclusion in the narrative report. Results: The PubMed search revealed a total of 1257 articles, of which 256 (20.4%) were considered relevant to OA imaging. Two-hundred twenty-six (87.1%) articles involved the knee joint, while 195 (76.2%) articles involved the use of magnetic resonance imaging (MRI). The proportion of published studies involving the use of MRI was higher than previous years. An increasing number of articles were also published on imaging of subjects with joint injury and on deep learning application in OA imaging. Conclusion: MRI and other imaging modalities continue to play an important role in research studies designed to better understand the pathogenesis, progression, and treatment of OA.
CRIS-Team Scopus Importer:2020-01-21
Keywords: Imaging; Magnetic resonance imaging; Osteoarthritis; Radiographs; Review